Necrotizing enterocolitis following treatment of congenital syphilis with penicillin in a term newborn - Charles Preston Pugh; Megan Baber; Gwenevere White (SAGE Open Medical Case Reports, 2023)
Necrotizing enterocolitis is a disease process of intestinal disruption which has been associated with gastrointestinal microbial alterations after antibiotic exposure. Treatment guidelines and antibiotic exposure for congenital syphilis have historically been based on limited evidence. This case presents a term infant who developed necrotizing enterocolitis after treatment for congenital syphilis.